(untitled) (Research, Society and Development, 2023)
Autism Spectrum Disorder (ASD) is a set of genetically variable neurodevelopmental disorders that manifests itself in dysfunctional social relationships and repetitive behaviors. Its prevalence has reached increasingly high rates, reflecting the need for health professionals to obtain knowledge to better approach this patient. The pediatric dentist, in turn, needs to use special techniques to be able to adapt the behavior of the patient with ASD to determine preventive and curative treatments in the dental environment. Thus, the aim of this study was to carry out a narrative review of the literature on oral conditions and factors in pediatric dental care for patients with Autism Spectrum Disorder. It was possible to conclude from this literature review that the knowledge and dissemination of information about ASD has positively affected the rate of early diagnosis in the child population. Patients with ASD have a higher frequency of caries, periodontal disease, oral lesions, dental trauma and malocclusion. Pedagogical techniques can help build oral health skills and facilitate understanding of dental procedures. Regarding sedation treatments, rigorous studies are still needed to define standardized medications, dosages and techniques in order to provide safe dental care for children with ASD.